الإبداع والتمكين الإداري – نظرة في واقع ثقافة الإبداع بالمؤسسة الجزائرية - د. – جامعة محمد بوضياف- المسيلة - الجزائر أ. – جامعة محمد بوضياف- المسيلة – الجزائر - ولد محي الدين, سعاد; إبراهيمي, أسماء (Université de M'sila, 2016)
تلعب الموارد البشرية دورا مهما في عملية اكتساب المنشاة ميزة تنافسية وذلك من خلال استثمارها استثمارا بهدف رفع الإنتاجية وتحسين الجودة بحيث أكدت الدراسات التي تمت أو أنجزت في مجال الجودة الشاملة أن أكثر من 75% من العاملين في المؤسسات اليابانية العاملة في مجال إنتاج السيارات والحاسبات الالكترونية والمصارف يشاركون بشكل مستمر في اجتماعات لها علاقة بتحسين العمليات الإنتاجية والجودة. ويرى أن علم الإدارة الحديث قد اهتم بالأفراد العاملين في المنظمة باعتبارهم الدعامة الرئيسية داخل المنظمة وقدراتها التنافسية وذلك من خلال تطبيق أحدث أساليب إدارة الموارد البشرية التي تعمل على رفع أداء العاملين ومن هذه الأساليب الحديثة أسلوب تمكين العاملين فهو يقوم على مشاركة العاملين في اتخاذ القرارات ومنحهم السلطة والنفوذ والقوة وتحمل المسؤولية في القرارات التي يتخذونها أو يشاركون في اتخاذها مع الإدارة العليا. إلا أن التمكين مهم لإثارة وإدارة الإبداع في المنظمات، حيث أن الجهود الإبداعية للعاملين تستمر بالرغم من انتشار العوائق البيئية والتنظيمية، وان امتلاك الحرية في اتخاذ القرار يحسن من مستوى الطاقة الإبداعية للعاملين وبالتالي يزيد من جودة الإنتاج ويرفع من مستوى المؤسسة. ومن خلال هذه المداخلة سنتطرق إلى واقع ثقافة الإبداع بالمؤسسة الجزائرية. Abstract: HR plays an important role in the acquisition of an entity competitive advantage process through investment investment in order to boost productivity and improve quality so that the studies that have been or completed in the field of Total Quality confirmed that more than 75% of workers in the Japanese institutions working in the field of cars, computers and electronic banking production engaged constantly in meetings related to the improvement of production processes and quality. He believes that the modern science of management may be concerned with the individuals working in the organization as the main pillar within the organization and their competitiveness through the application of the latest Human Resources, which is working to raise employee performance management techniques and the modern methods of approach to enable workers is based on the participation of workers in decision-making and give them power the influence and power and responsibility in the decisions they make, or participate in the take with senior management, However, the empowerment is important to raise and manage creativity in organizations, as the creative efforts of employees will continue in spite of the proliferation of environmental and regulatory barriers, and possession of freedom in decision-making improves the creative energy level for workers and thus increases the quality of production and raise the corporate level. Through this presentation we will look at the reality of the Algerian organization's culture of innovation.
Keywords: الإبداع التمكين الإداري